PEMAHAMAN SISWA KELAS IX SMPN 1 PONCOKUSUMO TERHADAP MATERI VOLUME BOLA MENGGUNAKAN PENDEKATAN PEMBELAJARAN SPICES - Sri Hariyani (Universitas Kanjuruhan Malang, 2013)
Various learning methods have been developed and can be divided into two major groups, namely the method based Teacher Centered Learning or known as the traditional approaches and teaching methods are based on Student Centered otherwise known as innovative approaches (SPICES approaches). SPICES is an acronym of (1) Student-centered, (2) Problem-based, (3) Integrated, (4) Community-based (Consumer-based), (5) Elective; and (6) Systematic. SPICES can be viewed as an advanced learning concepts and innovative and able to cope with problems that arise in relation to student learning. This concept was initiated by Harden, et al in 1984 and is widely practiced and developed in medical education. Therefore, the researchers tried to initiate a study to obtain a mathematical learning model that effectively and efficiently. SPICES is considered by the researchers were able to bridge the problems faced by teachers in relation to the hang of students. The objective of this study is a class IX SMPN I Poncokusumo. Selection of study subjects based on criteria such as academic ability of students is heterogeneous, the son of a passive more than active in class, and the daily tests that the average is still below 6.Â Kata Kunci : Volume bola, Pendekatan pembelajaran spices